Contribution of the D-Serine-dependent pathway to the cellular mechanisms underlying cognitive aging - Potier, Brigitte; Turpin, Fabrice R.; Sinet, Pierre-Marie; Rouaud, Emilie; Mothet, Jean-Pierre; Videau, Catherine; Epelbaum, Jacques; Dutar, Patrick; Billard, Jean-Marie (Frontiers in Aging Neuroscience, 2010)
An association between age-related memory impairments and changes in functional plasticity in the aging brain has been under intense study within the last decade. In this article, we show that an impaired activation of the strychnine-insensitive glycine site of N-Methyl-D-Aspartate receptors (NMDA-R) by its agonist D-serine contributes to deficits of synaptic plasticity in the hippocampus of memory-impaired aged rats. Supplementation with exogenous D-serine prevents the age-related deficits of isolated NMDA-R-dependent synaptic potentials as well as those of theta-burst-induced long-term potentiation and synaptic depotentiation. Endogenous levels of D-serine are reduced in the hippocampus with aging, that correlates with a weaker expression of serine racemase synthesizing the amino acid. On the contrary, the affinity of D-serine binding to NMDA-R is not affected by aging. These results point to a critical role for the D-serine-dependent pathway in the functional alterations of the brain underlying memory impairment and provide key information in the search for new therapeutic strategies for the treatment of memory deficits in the elderly.